2018
DOI: 10.1103/physreve.97.039901
|View full text |Cite
|
Sign up to set email alerts
|

Publisher's Note: Negative pressure in shear thickening band of a dilatant fluid [Phys. Rev. E 94 , 062614 (2016)]

Abstract: This corrects the article DOI: 10.1103/PhysRevE.94.062614.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Vorticity flow and dilatancy: The observation that the propagating stress fronts are associated with concentration fluctuations and flow in the vorticity direction is consistent with prior results showing that shear thickening is associated with fluctuations and localized dilatantcy [8,16,17,21,22,[26][27][28][29][30]. Fall et al [21] concluded that the excess suspension in Couette or an over-filled parallel plate rheometer geometries affected bulk rheology by providing a reservoir for particles forced out of the shearing region by dilatant pressure.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Vorticity flow and dilatancy: The observation that the propagating stress fronts are associated with concentration fluctuations and flow in the vorticity direction is consistent with prior results showing that shear thickening is associated with fluctuations and localized dilatantcy [8,16,17,21,22,[26][27][28][29][30]. Fall et al [21] concluded that the excess suspension in Couette or an over-filled parallel plate rheometer geometries affected bulk rheology by providing a reservoir for particles forced out of the shearing region by dilatant pressure.…”
Section: Discussionsupporting
confidence: 75%
“…Fall et al [21] concluded that the excess suspension in Couette or an over-filled parallel plate rheometer geometries affected bulk rheology by providing a reservoir for particles forced out of the shearing region by dilatant pressure. Experiments in a Couette geometry and associated continuum modeling have shown that dilatant fronts that propagate in the flow direction can occur in shear thickening [27,30]. Hermes et al [22] observed that rapid decreases in shear rate were accompanied by local deformations of the airsample interface at the edge of the rheometer tool, and that the deformations sometimes appear static and sometimes move opposite to the direction of the flow.…”
Section: Discussionmentioning
confidence: 99%
“…The complex rheological properties of a dense suspension result in various interesting phenomena, e.g., the stop-and-go (oscillatory) motion of a sinking ball in dense suspension [15,16] and oscillation in a rotating system [17]. These oscillatory behaviors may originate from the hysteresis of viscosity in a dense suspension [18] or the capillary effect [19].…”
Section: Introductionmentioning
confidence: 99%
“…The onset of frictional interactions will likely disrupt layering [19], a scenario confirmed by recent computer simulations [20]. A variety of evidence suggests that strong shear thickening is accompanied by complex spatiotemporal dynamics, including fluctuations in flow speed, local stress, and particle concentration [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. These results highlight the need for methods that can probe the dynamics of dense colloidal suspension with high spatial and temporal resolution.…”
Section: Introductionmentioning
confidence: 65%
“…These observations contribute to a growing body of evidence indicating that the shear thickening transitions typically involved complex spatiotemporal dynamics with structures propagating in the flow direction, including dilatant fronts [23,25], local deformations of the air-sample interface at the edge of the rheometer tool [26,31], local normal stresses in sheared cornstarch [30], concentration fluctuations appearing as periodic waves moving in the direction of flow [29], and high shear stress at the suspension boundary [27,32,33,35]. The specifics of the dynamics vary considerably, presumably indicating a sensitivity to the details of the suspension and the measurement geometry.…”
mentioning
confidence: 65%